The correlation of micro-teaching and teaching practice with the professional competence - Fuad, Varidlo; Samsuri, Samsuri; Brar, Balraj Singh (Harmoni Sosial: Jurnal Pendidikan IPS, 2022)
This research aims to know the correlation of micro-teaching and teaching practice with the professional competence of Civic Education students in LPTK in DIY. This research belongs to correlational research with a quantitative approach. The population of this research is students in the 7th semester or students who have passed micro-teaching thing classes and teaching practice programs (UNY, UAD, UPY, and UCY). The purposive sampling technique is used to determine the sample of the research. The 140 students from four Civic Education programs in the LPTK DIY are the sample of this research. The data were collected using question documentation. Data were analyzed using bivariate-experimental. The research results indicate a positive and significant correlation between teaching and teaching practice with the professional competence of the Civic Education students in LPTK in DIY. It can be proved from the signify, lower than 0.05, and the analysis of variance (ANOVA). Micro teaching and teaching effectively contribute about 58.4% to the professional competence of Civic students in LPTK in DIY.